Synthesis of activated carbon from salacca peel with hydrothermal carbonization for supercapacitor application. (2021) - Stenny Winata, Ashianti; Devianto, Hary; Frida Susanti, Ratna
Abstract: Supercapacitor is considered as a promising technology in the energy storage system (ESS) because of high power, large currents, and excellent cycle stability. In this study, activated carbon was used as the constituent material for electrodes because of its porous structure, a large surface area, high conductivity, low cost, and renewable. Activated carbon was synthesized from salacca peel by hydrothermal carbonization and chemical activation with KOH. In this research, the effect of operating pressure and temperature in the hydrothermal carbonization process was studied. The operating pressure was varied so that the water phase changed from vapor phase to liquid phase (subcritical water). The temperature was varied at 225 °C and 250 °C with a fixed carbonization time of 5 h. Chemical activation using KOH as an activating agent was done after obtaining the hydrochar from hydrothermal carbonization process. Produced activated carbons were characterized by nitrogen adsorption–desorption, scanning electron microscope, Fourier transform infrared, X-ray diffraction, and Raman spectroscopy. Electrochemical properties of these carbons were characterized by cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy. The research results showed that the largest surface area of produced activated carbons was 2907.31 m 2 /g (obtained by carbonization in subcritical water at 250 °C) while the largest capacitance of supercapacitor is 15.57F/g (obtained activated carbon produced by carbonization in saturated mixture at 250 °C).